Association between work status and depression in informal caregivers: a collaborative modelling approach. (25th November 2021) - O'Neill, Aoife; Gallagher, Stephen; Hannigan, Ailish; Robinson, Katie
Abstract: Background: Care is regularly provided on an informal basis by family and friends and it is well established that caregivers experience high rates of depression. The majority of research on caregivers tends to focus on older, full-time caregivers, with less attention paid to working caregivers (in paid employment). The aim of this study is to explore the impact of work status on depression in caregivers. Methods: A sample of individuals from the 2014 European Social Survey dataset, aged 18 and older, who reported being a caregiver, were investigated ( n = 11 177). Differences in sociodemographic, mental and physical health and social network variables, between working and non-working caregivers, were investigated. Hierarchical logistic regression models were used to investigate associations between the caregivers' work status and depression. This study was developed in partnership with a panel of caregivers who contributed to the conceptualization and interpretation of the statistical analysis. Results: Findings showed that 51% of caregivers reported being in paid employment. Non-working caregivers were more likely to be female, older, widowed, have lower education levels and provide intensive caring hours. They were also more likely to report depressive symptoms than working caregivers after controlling for sociodemographic, social networks and intensity of caring (adjusted odds ratio = 1.77, 95% confidence interval = 1.54–2.03). The panel considered policies to support continued work important as a means of maintaining positive mental health for caregivers. Conclusions: Supportive policies, such as flexible working and care leave, are recommended to allow caregivers to continue in paid work and better manage their health, caring and working responsibilities.